Land consolidation activities in Sub-Saharan Africa towards the agenda 2030: A tale of three countries. (February 2021) - Asiama, Kwabena Obeng; Voss, Winrich; Bennett, Rohan; Rubanje, Innocent
Highlights: There has been a new wave of land consolidation activities in Sub-Saharan Africa over the past two decades. Land tenure and household food security in Rwanda's LUC is lower as a result of the implementation approach. Current technical processes for land consolidation do not fit the land tenure structure on SSA's customary lands. Ethiopia's land consolidation is a bottom up flexible approach, sensitive to local needs. Land consolidation in SSA can contribute to SDGs such as food security, poverty reduction, and landscape management. Abstract: Land consolidation activities have generally failed in the Sub-Saharan African region for various reasons. However, there has been a new wave of land consolidation activities in the past two decades. This study examines how contemporary land consolidation activities in Sub-Saharan Africa contribute to the achievement of the SDGs, specifically ending poverty, ending hunger, and developing sustainable cities and settlements through land tenure security, food security, and rural development initiatives at country level. Using cases from Rwanda, Ethiopia, and Ghana, the study draws lessons on how land consolidation activities can contribute to the 2030 agenda. In Rwanda, it is found that though land use consolidation is a locally developed strategy for food security, due to its focus on the national level, household food security is actually lowering. Perceptions of land tenure security are also lower, despite an increase in legal tenure security. In Ghana, it is seen that the technical processes of land consolidation, though they hold the potential to increase food security, they will not fit with the existing land tenure system. Finally, in Ethiopia, it is seen that a bottom-up land consolidation is flexible and sensitive to local needs, however, scaling is difficult without the strong governmental involvement. Overall, land consolidation in SSA could deliver significantly to those SDGs relating to food security, poverty reduction, and landscape management. However, realistically, to achieve measurable country-wide or regional impact by 2030, immediate and strong governmental support tied to collaboration with community leadership is essential.